Molecular Prevalence and Risk Factors of Campylobacter Infection in Puppies in the Nairobi Metropolitan Region, Kenya - Sharon N. Mbindyo; Jafred M. A. Kitaa; Tequiero O. Abuom; Gabriel O. Aboge; Daniel W. Muasya; Beatrice W. Muchira; Nduhiu Gitahi; Charles M. Mulei (Veterinary Medicine International)
Campylobacter species are widely distributed pathogens; however, data on its epidemiology in puppies remain scanty, especially in Kenya. A cross-sectional study was conducted in the Nairobi Metropolitan Region to determine molecular prevalence and associated risk factors of Campylobacter species infection in puppies. A total of 260 rectal swabs were collected from puppies from breeding kennels, shelters, and the University of Nairobi Veterinary Teaching and Referral Hospital. The samples were subjected to polymerase chain reaction (PCR) assays for identification of Campylobacter species. Data on potential risk factors associated with puppy exposure were collected using a semistructured questionnaire. Multivariable mixed effects logistic regression analyses were performed with kennels as random effects. Campylobacter species were detected in 64 of the 260 sampled puppies yielding an overall prevalence of 24.6%. Multivariable results showed that puppies from shelters, puppies from kennels that are washed daily, puppies with a recent history of vomiting, and those treated with antibiotics in the past month were significantly associated with the presence of Campylobacter species. Being a kenneled puppy and having had concurrent bacterial infections were identified as protective factors. This study provides molecular evidence of puppy exposure to Campylobacter species which could have impact on puppy health and highlights the need to develop awareness and management strategies to potentially reduce the risk of transmitting this pathogen among puppies, to humans, and other animals.